Analisa Sel Sedimen Sebagai Pendekatan Studi Erosi Di Teluk Lampung, Kota Bandar Lampung Provinsi Lampung - Dianpurnama, Dianpurnama; Helmi, Muhammad; Yusuf, Muhammad (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro)
Shoreline deformation is a result from sediment transport process with an intervention of current. Concept of sediment cell used to facilitate the analysis and it can be seen on satellite images Landsat. The purpose of this research is to identify sediment cell limit and dominant direction of sediment transport along shore, erosion and sedimentation analysis using sediment cell approachment based satellite images analysis and wave modeling. This research used remote sensing method to determine sediment cell limit and ground check method to identify the source, direction and limits of sediments movement. The landmass that got erosion and accretion was obtained from satellite images overlay. Satellite images which used in this research is Landsat 1990, 2000 and 2010. According to the result of overlay, seashore deformation for 20 years was dominated by accretion (167,71 ha wider than erosion). The result of overlay showed that average accretion rate was 8,3855 ha/year and average erosion rate was 1,1745 ha/year. Results of overlay processing based on erosion and accretion showed that seashore in Bandar Lampung divided into 6 sub sediment cell with 5 limit of static sub cell and 1 dynamic sub cell appropriate for cell sediment concept.